Structural estimates of the intergenerational education correlation - Christian Belzil; Jörgen Hansen (Institute for the Study of Labor (IZA), 2003)
Using a structural dynamic programming model, we investigate the relative importance of family background variables and individual specific abilities in explaining cross-sectional differences in schooling attainments and wages. Given scholastic ability, household background variables (especially parents' education) account for 68% of the explained crosssectional variations in schooling attainments. When the effects of household background variables on ability are also taken into account, the percentage raises to 85%. However, individual differences in wages are mostly explained by abilities. Only 27% of the explained variation in wages is accounted for by parents? background variables as opposed to 73% by unobserved abilities (orthogonal to family background variables). When scholastic ability is correlated with family background variables, ability endowments explain as much as 81% of individual wages.
Keywords: J3; J2; 330; intergenerational education correlation; endogenous schooling; household characteristics; dynamic programming; Bildungsniveau; Bildungsökonomik; Soziale Mobilität; Generationenbeziehungen; Familiensoziologie; Dynamische Optimierung; Schätzung; Vereinigte Staaten